How much did pottery workers know about classical art and civilisation?. (1st September 2020) - Hall, Edith
Abstract: The voices of pottery workers across the British Isles during the heyday of the taste for classically themed ceramics are almost silent to us, since so few left memoirs or diaries. But other sources cumulatively build up a picture of skilled male, female, and child workers familiar with multifarious ancient artefacts and books visually reproducing them. At Etruria and Herculaneum, workers were encouraged to see themselves as participants in the rebirth of the ancient ceramic arts; they were trained in painstaking reproduction of details not only from ancient vases but from ancient gems, intaglios, ivories, coins, bas-reliefs, frescoes, friezes, statues, and sarcophagi. They were familiar with the stories of a substantial number of ancient mythical and historical figures, and the different aesthetic conventions of classical Athenian, Hellenistic, and Roman art. Some were even able to study antiquity at institutions of adult education, and had access to well-stocked workers' libraries.